2003
DOI: 10.1152/japplphysiol.00192.2003
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Do inflammatory mediators influence the contribution of airway smooth muscle contraction to airway hyperresponsiveness in asthma?

Abstract: It is now accepted that a host of cytokines, chemokines, growth factors, and other inflammatory mediators contributes to the development of nonspecific airway hyperresponsiveness in asthma. Yet, relatively little is known about how inflammatory mediators might promote airway structural remodeling or about the molecular mechanisms by which they might exaggerate smooth muscle shortening as observed in asthmatic airways. Taking a deep inspiration, which provides relief of bronchodilation in normal subjects, is le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 96 publications
2
45
0
1
Order By: Relevance
“…Longer actin filaments in people with asthma are not that hard to hypothesize, since the environment in asthmatic, inflamed airways is rife with cytokines and mediators that promote hypertrophy and hyperplasia in most of the tissues in the bronchiolar wall (28,29). Furthermore, it is well established that stress, stretch, and cytokines can directly activate p38 MAPK, an upstream regulator of HSP27 and actin filament length (23,24,31).…”
Section: Actin Filament Length As a Regulator Of Ffirmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer actin filaments in people with asthma are not that hard to hypothesize, since the environment in asthmatic, inflamed airways is rife with cytokines and mediators that promote hypertrophy and hyperplasia in most of the tissues in the bronchiolar wall (28,29). Furthermore, it is well established that stress, stretch, and cytokines can directly activate p38 MAPK, an upstream regulator of HSP27 and actin filament length (23,24,31).…”
Section: Actin Filament Length As a Regulator Of Ffirmentioning
confidence: 99%
“…Herrera and colleagues have demonstrated that associated actin (32) and myosin (25)(26)(27) filaments in TSM increase in length with contraction, and dynamically shorten and lengthen with airway smooth muscle cell migration (23,24). This dynamic nature of actin filament assembly and evanescence cannot be accounted for by the actin filamentstabilizing effects of such proteins as tropomyosin (29)(30)(31) or caldesmon (33,34). Therefore, we used pharmacologic tools to test the hypothesis that altering actin dynamics and therefore actin filament length would indeed modify FFIR of contracted airway smooth muscle.…”
Section: Actin Filament Length As a Regulator Of Ffirmentioning
confidence: 99%
“…As noted above, actin filament length is regulated through multiple pathways, many of which respond to external stimuli, including inflammatory stressors such as cytokines and growth factors known to be present in asthmatic airways (3). Perhaps the inflammatory environment of the asthmatic airway leads to abnormally long actin filaments in asthmatic airway myocytes that impart a reduced ability to relengthen with deep inspiration.…”
Section: Fig 6 Protocolmentioning
confidence: 99%
“…These drugs also have lower incidence of side effects and seem to be more suitable for clinical use [53]. Application of roflumilast was more effective in subjects with asthma [54], whereas cilomilast was more effective in COPD patients [55]. Lipworth et al [56] published the hypothesis that roflumilast could be as effective as beclometasone dipropionate in the treatment of moderate asthma; therefore it can be an alternative treatment and can replace the inhalative corticosteroids.…”
Section: Selective Phosphodiesterase Inhibitors (Pde)mentioning
confidence: 99%